Pyrenochaetopsis kuksensis (Pyrenochaetopsidaceae), a new species associated with an ornamental boxwood in the Czech Republic - Špetík, Milan; Berraf-Tebbal, Akila; Pokluda, Robert; Eichmeier, Aleš (Phytotaxa, 2021)
During the investigation of fungal microbiome associated with boxwood in the Czech Republic, samples from Buxus sempervirens L. (Buxaceae) plants were collected and used for isolation. Two fungal strains were proposed as a new species Pyrenochaetopsis kuksensis based on morphology as well as phylogenetic analyses of ITS, LSU, rpb2, and tub2 sequence data. Detailed descriptions and phylogenetic relationships of the new taxon are provided.